2014
DOI: 10.1016/j.chom.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma cruzi Flagellum Is Discarded via Asymmetric Cell Division following Invasion and Provides Early Targets for Protective CD8+ T Cells

Abstract: During invasion of host cells by Trypanosoma cruzi, the parasite that causes Chagas disease, the elongated, flagellated trypomastigotes remodel into oval amastigotes with no external flagellum. The underlying mechanism of this remodeling and the fate of the flagellum are obscure. We discovered that T. cruzi trypomastigotes discard their flagella via an asymmetric cellular division. The flagellar proteins liberated become among the earliest parasite proteins to enter the MHC-I processing pathway in infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 55 publications
3
52
1
Order By: Relevance
“…In contrast to CD8 + target epitopes encoded by paraflagellar rod proteins, which are detected in association with host cell surface MHC I within 6 hrs post-infection, the ts family epitopes are expressed relatively late in the infection cycle in host cells and are not visible to ts-specific T cells until between 24 and 48 hours post-infection (23). Thus, not only is the dominant CD8 + T cell response focused on a constantly changing and strain-variant array of targets but these targets are also expressed late in the host cell infection process, once again providing time for parasite expansion prior to target cell recognition.…”
Section: The Contribution Of Ts Proteins and Pamp Recognition To Immumentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to CD8 + target epitopes encoded by paraflagellar rod proteins, which are detected in association with host cell surface MHC I within 6 hrs post-infection, the ts family epitopes are expressed relatively late in the infection cycle in host cells and are not visible to ts-specific T cells until between 24 and 48 hours post-infection (23). Thus, not only is the dominant CD8 + T cell response focused on a constantly changing and strain-variant array of targets but these targets are also expressed late in the host cell infection process, once again providing time for parasite expansion prior to target cell recognition.…”
Section: The Contribution Of Ts Proteins and Pamp Recognition To Immumentioning
confidence: 99%
“…In addition to the “moving target” represented by constantly evolving but naturally immunodominant ts gene-encoded epitopes, these ts epitopes are also not presented by infected cells until relatively late in the infection cycle (23). The delay in ts epitope presentation may reflect the requirement for a sufficient number of ts-producing amastigotes to accumulate in the host cell cytoplasm and/or relate to huge number of ts variants being produced and thus competing for presentation by class I MHC molecules.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Merged differential interference contrast and fluorescent image of a trypomastigote of T. cruzi stained with anti-Par4 antibody that highlights the flagellum [16] (scale bar = 15 μm).…”
Section: Trypanosoma Cruzi Infectionmentioning
confidence: 99%
“…An important study indicated PAR4 as the target of T. cruzi-specific CD8+ T cell responses. Over expression of PAR4 improved PAR4-specific CD8+ T cell responses and provided significantly enhanced protection from infection; this chapter speculated that flagellar proteins can be used as antigens in potential vaccines against T. cruzi [72]. …”
Section: Paraflagellar Structure and Flagellum Attachment Zonementioning
confidence: 99%